The integration of cultural elements in the English language classrooms: a case study of selected Orang Asli schools in Pahang, Malaysia - Idrus, Faizah; Hussin, Muhammad Ekram; Gulca, Mahinur (Universiti Sultan Zainal Abidin, Malaysia, 2023)
Background and Purpose: This study examined the challenges faced by the Orang Asli students from the Jah Hut tribe and their reactions towards the integration of their cultural elements in learning the English language at two Orang Asli schools in Temerloh, Pahang, Malaysia. It also sought to investigate students’ and teachers’ motivation in learning and teaching the subject. Methodology: This critical qualitative inquiry employed a case study approach employing semi-structured interviews and non-participant classroom observations. A total of 14 participants were selected through purposive sampling technique, which consisted of ten Orang Asli students, three Orang Asli teachers, and one Malay teacher from two Orang Asli’s schools in Temerloh district. Findings: The findings indicated that integrating the Orang Asli’s own culture into the English lessons had captivated their interest immensely. The most motivating and stimulating lessons were centred around cultural celebrations, the use of the native language, cooking the Orang Asli delicacies, and parading and explaining their outfits and costumes. Teachers responded to the importance of Culturally Responsive Teaching strategies’ acceptance and use in the classrooms regardless of the composition of the students. Similarly, they felt that the knowledge of understanding the cultures of others is critical as it allows one to understand the struggles, and slowly develop a sense of appreciation towards differences. Contribution: The study highlights pertinent information regarding the issue of a ‘one size fits all curriculum’, especially in the teaching of the English language with the diversity of people in Malaysia. It also provides suggestions on classroom teaching strategies for multicultural classrooms. It also adds input to the existing literature on the integration of cultural elements in the teaching of the English language to the Orang Asli students.